From the history of St. Volodymyr University: Nazarii Antonovych Favorov - V. G. Napadysta (Ukrainian Cultural Studies, 2019)
The article reconstructs the life and analyzes the main thematic components of the creative heritage of Nazariy Antonovich Favorov (1820-1897), Doctor of Theology, a professor who for almost four decades (1859-1897) taught moral theology at the St. Vladimir University and was the rector of the university church. Ideological and political prejudices have led to the long neglect of a highly respected, recognized person both by university tutors corporation and a wide circle of the public. N. A. Favorov is the author of many works on moral theology, in particular, "Essays on the Moral Orthodox-Christian Doctrine", which had seven editions, were highly appreciated by colleagues and for a long time were considered an official textbook on moral theology in Russia. The moralist-theologian concentrates his attention on the problems of the origin of morality, correlation of the morality doctrine with religious and philosophical foundations, the characteristic features of the moral activity subject, freedom of will and substantiation of its significance for the moral existence of man, moral choice, moral qualities and their place and role in the human essence. It was established that the main topics of his creative ideas were predominantly determined by the problems, established in moral theology, but N.A. Favorov did not overlook the issues relevant for academic philosophizing in Ukraine and the Western European ethical discourse of the second half of the nineteenth century. The semantic accents in the substantiation of N.A. Favorov’s creative searches were based on the main provisions of the Orthodox religious doctrine. The work of N.A. Favorov, though not entirely original, has a thorough and holistic presentation of the main problems of the moral existence of man, widely spread in the educational space of Ukraine in the second half of the nineteenth century, making his creative legacy important and meaningful in the national historical and cultural context.